2004
DOI: 10.18785/gcr.1601.14
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Comparison of Two Species of Needlefish (Belonidae) in the Alvarado Lagoonal System, Veracruz, Mexico

Abstract: We compared the diets of Atlantic needlefish, Strongylura marina, and redfin needlefish, Strongylura notata, in the Alvarado lagoonal system, Veracruz, Mexico, and analyzed diet breadth and trophic overlap between the species. All fishes were collected monthly from June 2000 to July 2001 at twelve sampling stations. A total of 74 intestinal tracts from S. marina were analyzed. The diet of S. marina consisted of 25 prey types with fish being the dominate prey. In eighty-nine digestive tracts examined from S. no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…The six species of fish examined are considered to be marine migrants (Castro-Aguirre et al, 1999;Elliott et al, 2007) that use shallow waters as nurseries, refuge, and feeding grounds. They are carnivorous species, mainly piscivores with stenophagy and trophic specialization (Carr & Adams, 1973;Arceo-Carranza et al, 2004;Cocheret de la Morinière et al, 2004;Cruz-Escalona et al, 2005;Guevara et al, 2007). Even if many marine fish species exhibit marked changes in their diet according to the temporal availability of prey and life stage of individuals (Blaber, 1997;Platell et al, 1997;Hajisamae, 2009), our observations allow to say that five of them show a relatively homogeneous diet over time since the overall occurrence of these species within the study area is low (Gallardo-Torres et al, 2012).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The six species of fish examined are considered to be marine migrants (Castro-Aguirre et al, 1999;Elliott et al, 2007) that use shallow waters as nurseries, refuge, and feeding grounds. They are carnivorous species, mainly piscivores with stenophagy and trophic specialization (Carr & Adams, 1973;Arceo-Carranza et al, 2004;Cocheret de la Morinière et al, 2004;Cruz-Escalona et al, 2005;Guevara et al, 2007). Even if many marine fish species exhibit marked changes in their diet according to the temporal availability of prey and life stage of individuals (Blaber, 1997;Platell et al, 1997;Hajisamae, 2009), our observations allow to say that five of them show a relatively homogeneous diet over time since the overall occurrence of these species within the study area is low (Gallardo-Torres et al, 2012).…”
Section: Discussionmentioning
confidence: 76%
“…There are no reports on the feeding habits of this species in the Gulf of Mexico but, off the coast of Italy, Synodus saurus is also a piscivorous species that feeds on small fish like sardines and anchovies (Esposito et al, 2009). The needlefish, S. notata, is considered a piscivore (Carr & Adams, 1973;Arceo-Carranza et al, 2004) that obtains prey throughout the water column, as demonstrated by the presence of both demersal and pelagic components in the diet (Arceo-Carranza et al, 2004). Even if in this study juvenile and adult fish were analyzed, the low number of fish collected prevented to formally compare between size classes but it has been shown that this species displays ontogenetic changes in its diet (Arceo-Carranza, 2002;Hajisamae, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Así, juveniles y adultos de las especies de los géneros Strongylura, Tylosurus (Belonidae) e Hyporamphus (Hemiramphidae) habitan con frecuencia en sistemas estuarinos, tanto del norte (De Angelo et al, 2014;La Peyre y Birdsong, 2008;Tolan y Nelson, 2009), como del sur del golfo de México (Arévalo-Frías y Mendoza-Carranza, 2015;Castillo-Rivera et al, 2002Díaz-Ruiz et al, 2018;Raz-Guzmán et al, 2018;Vega-Cendejas y Hernández, 2004), donde pueden llegar a ser especies moderadamente abundantes (Collette, 2002). No obstante, existen pocos estudios publicados sobre la ecología de estas especies, lo cual en parte se puede deber a su poca importancia dentro de las grandes pesquerías (Arceo-Carranza y Chiappa-Carrara, 2015;Arceo-Carranza et al, 2004;Collette et al, 2019;Egbert y Rulifson, 2017;Porter y Motta, 2004).…”
Section: Introductionunclassified